Manufacturing Risk-Free Government Debt - Zhengyang Jiang; Hanno Lustig; Stijn Van Nieuwerburgh; Mindy Z. Xiaolan (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Governments face a trade-off between insuring bondholders and taxpayers. If the government fully insures bondholders by manufacturing risk-free zero-beta debt, then it cannot also insure taxpayers against permanent macroeconomic shocks over long horizons. Instead, taxpayers will pay more in taxes in bad times. Conversely, if the government fully insures taxpayers against adverse macro shocks, then the debt becomes risky, at least as risky as unlevered equity claim. As the world's safe asset supplier, the U.S. appears to have escaped this trade-off thus far, whereas the U.K. has not.
Keywords: E62; F34; G12; 330; fiscal policy; term structure; debt maturity; convenience yield